UV‐absorbing compounds in the coral Pocillopora damicornis : Interactive effects of UV radiation, photosynthetically active radiation, and water flow - Paul L. Jokiel; Michael P. Lesser; Michael E. Ondrusek (Limnology and Oceanography, 1997)
A direct relationship exists between irradiance of solar ultraviolet (UV) radiation and concentration of UV‐absorbing compounds, know as mycosporine‐like amino acids (MAAs), in the Hawaiian reef coral Pocillopora damicornis. However, MAA concentration is also influenced by flow regime and the irradiance of photosynthetically active radiation (PAR). High irradiances of UV radiation in reef environments are correlated with high PAR and high water velocity, because all three parameters diminish exponentially with increased depth. This correlation can also be found along horizontal gradients on reefs. The clearest water is typically found on outer reefs growing in oceanic water. These ocean reefs typically experience high water velocities due to ocean swell when compared to the more turbid lagoon reefs exposed only to small wind‐driven waves. Flow‐modulated photosynthetic rate seems to be a major factor affecting the observed changes in MAA concentration when P. damicornis is grown under different flow regimes and identical irradiances of UV and PAR radiation. High PAR and high water velocity significantly enhance the effect of increased UV radiation on MAA concentration.